Історія селянського руху 1917–1921 років у Харківській губернії: джерелознавчий аспект - Мотенко, Ярослав Володимирович; Шишкіна, Євгенія Костянтинівна (My University, 2018)
Стаття є результатом дослідження проблеми систематизації і використання джерел з історії селянського руху у Харківській губернії в 1917– 1921 роках. Існуючу джерельну базу запропоновано розділити на документальні джерела, періодичні видання і мемуарну літературу. Комплекс документальних джерел складається з опублікованих та неопублікованих актових і канцелярських матеріалів. До першої групи належать нормативно-правові документи. Матеріали другої групи становить протокольна документація і міжвідомче листування. Тенденційність авторських статей у періодичних виданнях зумовлює критичний підхід при їх використанні. З огляду на суб’єктивний характер мемуаристики при її вивченні варто застосовувати порівняльний аналіз, співставлення з документальним матеріалом.

This paper presents information dealing with systematization and using of sources on Kharkiv guberniya peasants’ movement in 1917–1921. The sources base of the question was proposed to be divided into documentary, periodical and memoir groups. Complex of documentary sources consists of published and unpublished acts and office papers. The first group includes normative-legal documents, which regulated land affairs, products requisitions and peasants’ duties, as well as government resolutions adjusting relationships with local population. Materials of second group involve proceedings, interdepartmental correspondence (reports, resumes, and telegrams) and appeals of governors to the population. These documents presents the most urgent regional problems of those date: troubles with products and fuel, struggle with peasants resistant movement, organization of peasants non-party conferences and elections to the Soviets. The bias character of most periodical articles authors demands criticism in the process of source using. Taking into account memoirs’ subjectivity it is necessary to make sources comparative analysis, collate them with documentary material.
Keywords: Українська революція 1917-1921 рр.; Харківська губернія; селянський рух; документальні джерела; мемуарна література; періодичні видання; Ukrainian Revolution of 1917–1921; Kharkiv guberniya; peasants’ movement; sources base; documents; periodic; memories